PRAKIRAAN CURAH HUJAN KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT DENGAN MODEL AUTOREGRESIVE INTEGRATED MOVING AVERAGE (ARIMA) - Loupatty, Grace (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2007)
Forecasting is an activity to use the past data as the basic to predict the future event that will occur. The result from the prediction is an un-sure event or just a guess, but with some certain methods then the prediction will be more than a guess, it means that it is a scientific guess. The data analysis technique with autoregressive integrated moving average (ARIMA) method can give the early information that is needed as the material for the consideration to take the decision and the action itself